PENGEMBANGAN MODUL PEMBELAJARAN TEKS BIOGRAFI UNTUK PENGUATAN LITERASI SISWA KELAS X MAN 2 Jember - Zahrah, Amaliatuz; Amilia, Fitri; Citraningrum, Dina Merdeka (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to develop a learning module for biographical texts designed to improve the literacy of students in class X MAN 2 Jember. The research method used is Research and Development (R&D), with the stages of needs analysis, module design, expert validation, field trials, and evaluation. This module is structured with a literacy-based approach that integrates interactive elements, such as discussion, reflective writing, and value analysis of biographical figures. The results of the study show that this module is feasible to use based on the validation of linguists, materials, and media, with a high average score on linguistics, material suitability, and design aspects. The modules developed are able to increase student involvement in learning, strengthen critical thinking skills, and connect learning of biographical texts with daily life. Thus, this module can be an effective and relevant learning tool to strengthen students' literacy.